A comment on "Optimal Deposit Insurance" - Julia Chahine; Matthew DeHaven; Moritz Greiwe; Hyeonseo Lee; Zhuorong Mao (Institute for Replication (I4R), 2025)
Dávila and Goldstein (2023) examine the optimal determination of deposit insurance in the case where bank runs are possible. They provide a small set of sufficient statistics to determine welfare impacts of changes in deposit insurance coverage, and apply their framework using US data from 2008. In our replication, we focus on the quantitative application of the paper. First, we are trying to computationally reproduce table 1, section IV, that is used to estimate the marginal effect of changing deposit coverage. We can calculate sufficient statistics analogously to the ones of table 1 for 2011, but could not access data for the specific time period of the paper. However, our calculations produce values close to the average implied default probability for the post-financial crises period from 2012-2014 calculated by the authors. Second, we replicate the simulation results used to determine the optimal level of coverage, as well as conduct robustness checks for their calibration. We ran a sensitivity analysis on how the changes in the sunspot probability and bank's riskiness parameters affect the optimal insurance coverage, and obtained the same results as in the paper.
Keywords: 330